Partisan politics and the British fiscal-military state, 1689-1713 - Graham, A (2011)
The rapid expansion in the size and effectiveness of the British fiscal-military state between 1689 and 1713 has been analysed by historians such as John Brewer and Michael Braddick as the outcome of increasingly impartial, rational and professional bureaucratic administration. Yet recent work on state formation in Britain and Europe has emphasised that effectiveness often arose from practices usually dismissed as inefficient or corrupt. This thesis provides a new paradigm by comparing fiscal-military structures to contemporary commercial enterprises, which functioned by coordinating the efforts of suppliers and buyers. Coordination was achieved in turn through mutual trust, which overcame principal-agent problems and reduced transaction costs. This thesis suggests that by analogy, those polities that could encourage cooperation and mutual trust between autonomous officials, agencies and private contractors enjoyed the greatest success as fiscal-military states. In the mercantile or financial world trust was created through kinship and friendship, as well as common religious, ethnic or national identities, which contained inbuilt informal mechanisms for policing behaviour. This thesis examines the financing and supply of the British army in Ireland and Europe between 1689 and 1713 to conclude that these elements also served to create trust within state structures, and that even political partisanship – normally dismissed as a disruptive, even destructive, influence – generated a community of shared political interests that encouraged trust and improved coordination. It also demonstrates that officials, politicians and financiers constructed politicised networks that interlocked efficiently with each other, permitting the improved coordination of public and private credit, and even informal financial intermediation intended to maintain the liquidity of the army’s fiscal structures. It therefore concludes that the success of the British fiscal-military state during this period was the product of improved informal coordination rather than institutional change and bureaucratic reform, and that political partisanship was integral to this process.